The impact of COVID-19 on accelerating of immunosenescence and brain aging - Ludmila Müller; Svetlana Di Benedetto (Frontiers in Cellular Neuroscience)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has profoundly impacted global health, affecting not only the immediate morbidity and mortality rates but also long-term health outcomes across various populations. Although the acute effects of COVID-19 on the respiratory system have initially been the primary focus, it is increasingly evident that the virus can have significant impacts on multiple physiological systems, including the nervous and immune systems. The pandemic has highlighted the complex interplay between viral infection, immune aging, and brain health, that can potentially accelerate neuroimmune aging and contribute to the persistence of long COVID conditions. By inducing chronic inflammation, immunosenescence, and neuroinflammation, COVID-19 may exacerbate the processes of neuroimmune aging, leading to increased risks of cognitive decline, neurodegenerative diseases, and impaired immune function. Key factors include chronic immune dysregulation, oxidative stress, neuroinflammation, and the disruption of cellular processes. These overlapping mechanisms between aging and COVID-19 illustrate how the virus can induce and accelerate aging-related processes, leading to an increased risk of neurodegenerative diseases and other age-related conditions. This mini-review examines key features and possible mechanisms of COVID-19-induced neuroimmune aging that may contribute to the persistence and severity of long COVID. Understanding these interactions is crucial for developing effective interventions. Anti-inflammatory therapies, neuroprotective agents, immunomodulatory treatments, and lifestyle interventions all hold potential for mitigating the long-term effects of the virus. By addressing these challenges, we can improve health outcomes and quality of life for millions affected by the pandemic.